2019
DOI: 10.4236/wjcd.2019.93021
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and Associated Factors during Arterial Hypertension in Brazzaville (Congo)

Abstract: A longitudinal analytical and comparative study including outpatients was carried between June 1 st and December 31 st 2017. The objectives were to determine the hyperuricemia frequency during arterial hypertension, to identify associated factors, and to evaluate its impact on the blood pressure control. We have included, hypertensive patients having a minimum blood test including at least an uricemia. They were divided into two groups according to whether they have presented a hyperuricemia (HU) or a normouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
1
1
1
Order By: Relevance
“…This rate is higher than those reported by several studies such as in Libreville (10.3%) and Rabat (6.1%) [3] [23]. Our rate was lower than that collected in Brazzaville (20.2%) among elderly people with an estimated average age of 70.4 years [11]. This difference in frequency could take place, on the one hand, by the fact that ours was carried out in a medical structure without a cardiology intensive care unit, let alone a cardiac catheterization room, like the studies carried out at the University Hospitals of Libreville and Rabat.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This rate is higher than those reported by several studies such as in Libreville (10.3%) and Rabat (6.1%) [3] [23]. Our rate was lower than that collected in Brazzaville (20.2%) among elderly people with an estimated average age of 70.4 years [11]. This difference in frequency could take place, on the one hand, by the fact that ours was carried out in a medical structure without a cardiology intensive care unit, let alone a cardiac catheterization room, like the studies carried out at the University Hospitals of Libreville and Rabat.…”
Section: Discussioncontrasting
confidence: 79%
“…The role of traditional therapists plays a significant role, an observation also made by some authors [4]. The main etiologies were dominated by hypertensive heart disease, this etiology was widely found in several [3] [4] [11] [13] [14]. The THESUS-HF study carried out in nine sub-Saharan countries also highlighted the supremacy of hypertensive heart disease in our countries [19].…”
Section: Discussionsupporting
confidence: 62%
“…The main electrocardiographic anomaly found is complete arrhythmia due to atrial fibrillation with a percentage significantly higher than that found by Awa THIAW (11.1%) as well as Ikama MS and his collaborators (14.35%) [17,18]. LVEF, an important index of severity and poor prognosis of heart failure, was altered in more than two-thirds of patients, whereas McAlister et al found in their study carried out in the cardiology department in CANADA in 2004 an altered LVEF in 57% [19].…”
Section: Resultsmentioning
confidence: 99%